O parcelamento do solo para fins urbanos no município de São Roque (SP) analisado à luz da legislação ambiental - Cano, Jonas Miranda (Paisagem e Ambiente, 1995)
This essay analyses urban settlements process relating itto the legislation of urban land plottings and of environmental protection. Legal dispositions were plotted in four sample areas with about 4 km2 (2 km X 2 km) located in São Roque (SP) municipal district. The areas were selected inthe way ofcomprisi ng different stages and patterns of urban settlements and different natural environmental contexts, principally geomorphological and hidrographical ones. The areas legally destinated to environmental protection (borders and riverheads of bodies of water, mountain tops and high-declivity areas) were delimitated and size-calculated. These values were related to the minimum limits imposed by law for public spaces, including recreation and leisure areas, and to hypothetic absolute and relative population densities. Based on results, one concluded: 1) urban spreading in São Roque has being proceedi ng in absence of conditions due to the law, specially the environmental one; 2) putting the law into practice would create a lessenvorinment- and landscapechangeable human settlements, remaini ng many areas to be urban-plotted; 3) land uses would be arranged based on social-economic and envirnmental criteria, wherein environment characteristcs themselves would regulate land uses distribution. Finally, it is made a comment upon legislation for the extreme situation, of difficult practice